(untitled) (Perner’s Contacts, 2020)
This paper deals with a brief description of indentation modeling into hard and brittle materials, such as glass, laminated glass or various types of ceramics using the finite element method. The created model is very useful as a support for the indentation test because in this way we obtain other material characteristics that are difficult or even impossible to obtain experimentally, but also due to the detection of sources of measurement inaccuracies. Another benefit is the ability to investigate the response of an unknown combination of laminates and assess the suitability for use for a given purpose without the need to pre-fabricate the sample.